1991
DOI: 10.1128/jvi.65.12.6881-6891.1991
|View full text |Cite
|
Sign up to set email alerts
|

Cloning of the mouse hepatitis virus (MHV) receptor: expression in human and hamster cell lines confers susceptibility to MHV

Abstract: The cellular receptor for murine coronavirus mouse hepatitis virus (MHV)-A59 is a member of the carcinoembryonic antigen (CEA) family of glycoproteins in the immunoglobulin superfamily. We isolated a cDNA clone (MHVR1) encoding the MHV receptor. The sequence of this clone predicts a 424-amino-acid glycoprotein with four immunoglobulinlike domains, a transmembrane domain, and a short intracytoplasmic tail. MHVR, is closely related to the murine CEA-related clone mmCGM, (Mus musculus carcinoembryonic antigen gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
260
0
1

Year Published

1994
1994
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 316 publications
(265 citation statements)
references
References 63 publications
3
260
0
1
Order By: Relevance
“…CoVs exploit a limited variety of proteinaceous receptors compared with the large number and diversity of viral species. All CoVs known to engage proteinaceous receptors do so using domain B with the exception of MHV, which binds CEACAM1a using domain A (Dveksler et al, 1991;Peng et al, 2011;Williams et al, 1991). Remarkably, viruses from different genera, such as HCoV-NL63 (α-CoV) and SARS-CoV (β-CoV), can recognize the same region of ACE2 (entry receptor) using structurally distinct B domains (Hofmann et al, 2005;Li et al, 2005aLi et al, , 2003Wu et al, 2009).…”
Section: Diversity Of Cov Receptors and Entry Mechanismsmentioning
confidence: 99%
“…CoVs exploit a limited variety of proteinaceous receptors compared with the large number and diversity of viral species. All CoVs known to engage proteinaceous receptors do so using domain B with the exception of MHV, which binds CEACAM1a using domain A (Dveksler et al, 1991;Peng et al, 2011;Williams et al, 1991). Remarkably, viruses from different genera, such as HCoV-NL63 (α-CoV) and SARS-CoV (β-CoV), can recognize the same region of ACE2 (entry receptor) using structurally distinct B domains (Hofmann et al, 2005;Li et al, 2005aLi et al, , 2003Wu et al, 2009).…”
Section: Diversity Of Cov Receptors and Entry Mechanismsmentioning
confidence: 99%
“…Coronaviruses can also be retargeted to specific cells by exchanging the ectodomain of the S protein for that of an appropriate other coronavirus, as was demonstrated for MHV (Kuo et al, 2000) and FIPV (Haijema et al, 2003). Receptors have so far been identified for the group 2 coronavirus MHV (CEACAM; Dveksler et al, 1991Dveksler et al, , 1993Williams et al, 1991); the group 1 coronaviruses TGEV and porcine respiratory coronavirus (PRCoV) (pAPN; Delmas et al, 1992T resnan et al, 1996), and HCoV-229E (hAPN; Yeager et al, 1992); and for SARS-CoV (ACE2; Li et al, 2003). The S proteins of the group 2 coronaviruses have been observed to exhibit hemagglutinating activities.…”
Section: F S Proteinmentioning
confidence: 99%
“…The major structural proteins of MHV virion include the spike glycoprotein (S) the envelope protein (E) the membrane protein (M) and the nucleocapsid protein (N). Although the multifunctional protein N contributes to the pathogenic outcome of coronavirus infection (Cowley et al, 2010), the MHV S protein plays a major role in the pathogenesis since it recognizes and binds the cellular receptor for the virus, Ceacam1a, mediates cell entry by inducing fusion of viral and cell membranes, subsequently facilitates virus spread to other cells by inducing cell to cell fusion (syncytium formation) at late times in infection when the S protein is abundantly present on the plasma membrane of infected cells (Dveksler et al, 1991), and recently it was found to regulate the intracellular transport of the viral genome from the cell surface to the ER (Zhu et al, 2009). S is also a major target of the host immune response, eliciting neutralizing antibodies and CD8+ cytotoxic T cell responses (Castro and Perlman, 1995).…”
Section: Introductionmentioning
confidence: 99%